The Impact Of Interface Design On Customer Adoption Of Internet Banking - Mohamad @Abd Majid, Suriani (2003)
This paper focuses on the element of intercafe design that might contribute to greater customer adoption of internet banking. It is hoped that this study could contribute to improvements in interface design and hence foster better adoption by the customers in the near future.